TET1 promotes 5hmC-dependent stemness, and inhibits a 5hmC-independent epithelial-mesenchymal transition, in cervical precancerous lesions. (28th May 2019) - Su, Po-Hsuan; Hsu, Yaw-Wen; Huang, Rui-Lan; Chen, Lin-Yu; Chao, Tai-Kuang; Liao, Chi-Chun; Chen, Chien-Wen; Wu, Tzu-I.; Mao, Shih-Peng; Balch, Curt; Lai, Hung-Cheng
Abstract: DNA hypermethylation is a driving force in carcinogenesis. However, the role of active DNA hypomethylation in cancer remains largely unknown. This process, facilitated by ten-eleven translocation methylcytosine dioxygenase 1 (TET1), which oxidizes 5-methylcytosine (5 mC) to 5-hydroxymethylcytosine (5hmC), has never been studied in cervical cancer. Here, we found that TET1 and 5hmC correlative increases from normal cervix to Low-grade squamous intraepithelial lesion (LSIL), maximizing in High-grade squamous intraepithelial lesion (HSIL), and decreasing in invasive cancer. Full-length HPV-immortalized HSIL cells demonstrated higher TET1/5hmC levels, and stemness properties, compared to invasive cancer cells. TET1 silencing promoted the epithelial-mesenchymal transition (EMT), to transform precancerous cells in vivo . TET1 increased 5hmC in the ZEB1 and VIM promoters, surprisingly, silencing both genes. TET1 interaction with the histone modifiers, LSD1 and EZH2, on the ZEB1 promoter, resulted in gene silencing, via loss of histone H3K4 trimethylation, and gain of histone H3K27 trimethylation. Taken together, TET1 promotes stemness properties, and inhibits EMT, in HSIL cells, through 5hmC-dependent and -independent mechanisms. Highlights: TET1/5hmC increases from normal cervix, greatest in HSIL, and decreasing in cancer. TET1 promotes stemness and inhibits EMT via 5hmC-dependent and -independent manner. Loss of TET1 promotes EMT and transforms precancerous cells to become tumorigenic. TET1 interacts with histone modifiers, LSD1 and EZH2 and results in gene silencing.